2019
DOI: 10.32098/mltj.01.2017.07
|View full text |Cite
|
Sign up to set email alerts
|

Conservative, minimally invasive and open surgical repair for management of acute ruptures of the Achilles tendon: a clinical and functional retrospective study

Abstract: Background: Achillodynia is common and includes Achilles tendinopathy, partial Achilles tears and Achilles tendon ruptures. However, we believe an additional pathology should be considered for Achillodynia differentials -the intratendinous tear (ITT). Methods: Examinations of 740 achillodynic patients in one specialist centre were reviewed. ITTs were defined as a clearly visualised echopoor area situated centrally and extending to, but not through the tendon periphery, with pain on palpation and no clinical fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…A post-operative protocol described by Maffulli et al [ 94 ] let patients to be discharged the same day of the operation and allowed them to bear weight on the metatarsal heads of the operated leg using elbow crutches as tolerated. An orthopedic physiotherapist should instruct the patient to use crutches.…”
Section: Principles Of Rehabilitationmentioning
confidence: 99%
“…A post-operative protocol described by Maffulli et al [ 94 ] let patients to be discharged the same day of the operation and allowed them to bear weight on the metatarsal heads of the operated leg using elbow crutches as tolerated. An orthopedic physiotherapist should instruct the patient to use crutches.…”
Section: Principles Of Rehabilitationmentioning
confidence: 99%
“…Some people advocate conservative treatment, while others surgical treatment, both of which have positive effects (20). However, a study has shown that surgical treatment reduces the incidence of re-rupture of Achilles tendon (21), therefore surgical treatment is considered to be slightly superior to conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although some of the recent literature credits percutaneous repair with having fewer postoperative complications, the overall functional outcome remains more favorable when treated via an open technique. Despite postoperative concerns for acute Achilles tendon rupture treated with open repair, it continues to have decreased tendon rerupture rates (75,81,87−89), lower rates of decreased calf circumference (77), and decreased incidence of sural neuritis (77,78,85). Based on the findings from the majority of recent literature published, it is inappropriate to depict percutaneous repair of acute Achilles tendon ruptures as having better overall functional outcomes compared with traditional open repair.…”
Section: Smokingmentioning
confidence: 99%